Sell‐Side School Ties - COHEN, LAUREN; FRAZZINI, ANDREA; MALLOY, CHRISTOPHER (Journal of Finance, 2010)
ABSTRACT We study the impact of social networks on agents’ ability to gather superior information about firms. Exploiting novel data on the educational background of sell‐side analysts and senior corporate officers, we find that analysts outperform by up to 6.60% per year on their stock recommendations when they have an educational link to the company. Pre‐Reg FD, this school‐tie return premium is 9.36% per year, while post‐Reg FD it is nearly zero. In contrast, in an environment that did not change selective disclosure regulation (the U.K.), the school‐tie premium is large and significant over the entire sample period.